Thermally Stable Phosphonium Organoclay-Reinforced Polyimide Nanocomposites - ÇAKMAKÇI, EMRAH; BİRTANE, HATİCE; KAHRAMAN, MEMET VEZİR (TAYLOR & FRANCIS INC, 2017)
To prepare clay containing high-temperature processable polymer nanocomposites, new cation exchangeable agents with high thermal stability are required. In this work, we investigated the effect of a thermally stable phosphonium-modified organoclay on the properties of polyimides prepared from the reaction of 4,4-oxydianiline with 3,3,4,4-benzophenonetetracarboxylic dianhydride. The organoclay was prepared from the reaction of pristine clay with octyltriphenylphosphonium bromide. Phosphonium-modified clay displayed a negligible weight loss (<5%) below 300 degrees C. The thermal stability of the composites enhanced with the increasing amount of phosphonium-modified clay.
Keywords: Differential scanning calorimetry; nanocomposites; organoclay; polyimides; CLAY NANOCOMPOSITES; MECHANICAL-PROPERTIES; MONTMORILLONITES; COMPOSITES; HYBRIDS